1989
DOI: 10.1056/nejm198906083202304
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Theophylline in Patients with Severe Chronic Obstructive Pulmonary Disease

Abstract: To assess the effects of theophylline in chronic obstructive pulmonary disease, we conducted a randomized, placebo-controlled, double-blind, crossover trial in 60 patients with severe but stable disease. The patients (mean age, 61 years) were studied before and after two months of placebo and two months of treatment with a sustained-release preparation of theophylline (10 mg per kilogram of body weight per day), administered orally. The two treatments were administered in a random order and separated by an eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
64
0
7

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(79 citation statements)
references
References 15 publications
8
64
0
7
Order By: Relevance
“…Thirdly, shortness of breath (according to mMRC scale), was improved in 65% patients of group-1 and 45% patients of group-2. These findings are in agreement with the study by Giovanni Agliati [6], E. Pozzi [7], Danièle Murciano et al, [8], Donald A Mahler [9], and H.Weber [11]. There was no deterioration among patients of Acebrophylline group but breathlessness deteriorated in 35% patients on SR Theophylline.…”
Section: Discussionsupporting
confidence: 91%
“…Thirdly, shortness of breath (according to mMRC scale), was improved in 65% patients of group-1 and 45% patients of group-2. These findings are in agreement with the study by Giovanni Agliati [6], E. Pozzi [7], Danièle Murciano et al, [8], Donald A Mahler [9], and H.Weber [11]. There was no deterioration among patients of Acebrophylline group but breathlessness deteriorated in 35% patients on SR Theophylline.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that longterm theophylline use for COPD patients results in improvement of pulmonary functions, indicating that theophylline has a beneficial effect on exacerbation of COPD. 25,26) Therefore, we examined the effect of theophylline on the functional structural changes in our model. …”
mentioning
confidence: 99%
“…The risk of side effects increases with higher theophylline concentrations, and the majority of seizures occur in patients with concentrations greater than 40 μg/mL [52][53][54]. Further reports suggest that peak serum theophylline concentrations were a predictor of toxicity [55][56][57]. Even so, no consensus guidelines existed for when to employ hemoperfusion, with threshold serum theophylline levels ranging from 330 (59.4) to 550 μmol/L (99 μg/mL) [10,58,59].…”
Section: What Are the Indications For Hemodialysis Or Hemoperfusion Fmentioning
confidence: 99%
“…While caffeine is used for stimulant and mood-elevating effects in drinks such as coffee, it also has been used to treat neonatal apnea and headaches in combination with other analgesics. Theophylline has classically been used to treat bronchospastic airway diseases such as asthma and COPD, although it has generally fallen out of favor to pure β-adrenergic agonists due to their better safety profiles [2]. As a group, methylxanthines cause the release of catecholamines, which subsequently stimulate β 1 and β 2 receptors, accounting for their stimulant effects.…”
mentioning
confidence: 99%